2009
DOI: 10.1098/rspb.2009.1591
|View full text |Cite
|
Sign up to set email alerts
|

Colony fusion and worker reproduction after queen loss in army ants

Abstract: Theory predicts that altruism is only evolutionarily stable if it is preferentially directed towards relatives, so that any such behaviour towards seemingly unrelated individuals requires scrutiny. Queenless army ant colonies, which have anecdotally been reported to fuse with queenright foreign colonies, are such an enigmatic case. Here we combine experimental queen removal with population genetics and cuticular chemistry analyses to show that colonies of the African army ant Dorylus molestus frequently merge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 50 publications
(61 reference statements)
1
42
0
Order By: Relevance
“…In agricultural areas and savanna-like vegetation at 1100 m asl we found ants belonging to a D. (Typhlopone) species at four baits, whereas 51 of the 53 samples collected at the three other sites belonged to species in the subgenera Dorylus s.s. and Rhogmus and two belonged to D. molestus. Males of a D. (Typhlopone) species were collected at light sources just below the forest at around 1600 m asl but dispersal distances of the large Dorylus males are apparently very long (Kronauer et al, 2010). More extensive sampling is therefore required to determine whether colonies of this species occur in the agricultural area close to the forest.…”
Section: Simulating Attacks By Mammalian Predatorsmentioning
confidence: 99%
“…In agricultural areas and savanna-like vegetation at 1100 m asl we found ants belonging to a D. (Typhlopone) species at four baits, whereas 51 of the 53 samples collected at the three other sites belonged to species in the subgenera Dorylus s.s. and Rhogmus and two belonged to D. molestus. Males of a D. (Typhlopone) species were collected at light sources just below the forest at around 1600 m asl but dispersal distances of the large Dorylus males are apparently very long (Kronauer et al, 2010). More extensive sampling is therefore required to determine whether colonies of this species occur in the agricultural area close to the forest.…”
Section: Simulating Attacks By Mammalian Predatorsmentioning
confidence: 99%
“…However, we suspected that queenless colonies may sometimes merge with nearby conspecific colonies, as has been observed in the Cape honey bee A. m. capensis (Neumann et al, 2001) and the African army ant Dorylus molestus (Kronauer et al, 2009). Furthermore, we have previously reported that A. florea workers are occasionally found in A. andreniformis nests in unmanipulated colonies (Wongvilas et al, 2010).…”
Section: Introductionmentioning
confidence: 96%
“…Two recent studies exclude the possibility of social parasitism and drift, causing the authors to postulate that colony mergers (Kronauer et al, 2009), and drifting (Sumner et al, 2007), occur because population viscosity leads to non-zero relatedness among nests. Thus, it is suggested that non-natal workers increase their inclusive fitness if they join and work for a nearby colony, for they will have at least some relatedness to it.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations